2006
DOI: 10.1086/503290
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric 890 μm Images of High-Redshift Submillimeter Galaxies

Abstract: We present high-resolution 890 mm images of two 20 mJy submillimeter galaxies, SMM J123711ϩ622212 and MIPS J142824.0ϩ352619, obtained using the Submillimeter Array (SMA). Using submillimeter interferometric observations with an angular resolution of 2Љ .5, the coordinates of these high-redshift sources are determined with an accuracy of 0Љ .2. The new SMA data on SMM J123711ϩ622212 reveal an unresolved submillimeter source offset to the east by 0Љ .8 from an optical galaxy found in deep HST images, suggesting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 34 publications
8
112
0
Order By: Relevance
“…This is particularly interesting for this sample of the brightest sources in the AzTEC/COSMOS catalog because it rules out blends of multiple fainter sources as a significant contributor to the upper end of the observed SMG luminosity function. It also agrees with previous interferometric measurements of the angular extent of the millimeter (Downes et al 1999;Genzel et al 2003;Downes & Solomon 2003;Kneib et al 2005;Tacconi et al 2006) and submillimeter (Iono et al 2006) emission from SMGs, and marginally with those of the radio continuum (Chapman et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is particularly interesting for this sample of the brightest sources in the AzTEC/COSMOS catalog because it rules out blends of multiple fainter sources as a significant contributor to the upper end of the observed SMG luminosity function. It also agrees with previous interferometric measurements of the angular extent of the millimeter (Downes et al 1999;Genzel et al 2003;Downes & Solomon 2003;Kneib et al 2005;Tacconi et al 2006) and submillimeter (Iono et al 2006) emission from SMGs, and marginally with those of the radio continuum (Chapman et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Previous interferometric observations at millimeter (Downes et al 1999;Frayer et al 2000;Dannerbauer et al 2002;Downes & Solomon 2003;Genzel et al 2003;Kneib et al 2005;Greve et al 2005;Tacconi et al 2006) and submillimeter (Iono et al 2006) wavelengths have identified unambiguous counterparts for increasing numbers of radio-detected SMGs, and have confirmed the radio-submillimeter association. However, to date there has been no reliable highresolution followup of a uniformly selected sample including radio-undetected SMGs, and the true nature of these sources therefore remains elusive.…”
Section: Introductionmentioning
confidence: 87%
“…Before the improved sensitivities provided by the upgraded IRAM PdBI or ALMA, interferometric follow-up at millimeter or submillimeter wavelengths was slow and expensive. Only about 50 SMGs have been properly identified in various survey fields (Downes et al 1999, Frayer et al 2000Dannerbauer et al 2002;Downes & Solomon 2003;Genzel et al 2003;Kneib et al 2005;Greve et al 2005;Tacconi et al 2006;Sheth et al 2004, Iono et al 2006Younger et al 2007Younger et al , 2009Aravena et al 2010a;Ikarashi et al 2011;Tamura et al 2010;Hatsukade et al 2010;Wang et al 2011;Chen et al 2011;Neri et al 2003;Chapman et al 2008;Smolčić et al 2012). The largest statistically significant, signal-to-noise-and flux-limited sample of interferometrically identified SMGs contains 17 sources drawn from the AzTEC/JCMT survey of 0.15 • within the COSMOS field (Younger et al 2007(Younger et al , 2009).…”
Section: Identifying Multi-wavelength Counterparts To Smgsmentioning
confidence: 99%
“…Ivison et al 2002Ivison et al , 2005Pope et al 2006;Hainline et al 2009;Yun et al 2008Yun et al , 2012. Deep intermediate-resolution radio observations, which are less time consuming than similar mm-wave observations, but are expected to trace the same physical processes (given the IR-radio correlation; e.g.…”
Section: The Biases Of Assigning Counterparts To Single-dish Detectedmentioning
confidence: 99%
See 1 more Smart Citation